Dyskusje na temat pomnika Adama Mickiewicza w Wilnie na łamach prasy wileńskiej z lat 1925–1927 - Fedorowicz, Irena (Slavistica Vilnensis, 2011)
Irena FedorovichDiscussions on the Project of A. Mickiewicz’s Monument in Vilna in Press of 1925–1927The first monument in honour of A. Mickiewicz in Vilna was a bust unveiled in the church of Saint Johns ’ in 1899. However, the Vilnius town-dwellers were willing to erect a monument in a public place. This topic stimulated lots of emotions, especially in the years 1925–1927. Readers of the daily newspapers “Word” (“Słowo”) and “Courier of Vilna” (“Kurier Wileński”) were divided into supporters and opponents of the project of the monument of A. Mickiewicz created by the sculptor S. Szukalski. He was the winner of the competition held in 1926. Under the pressure of public opinion that project was never materialized.Discussion on the monument to A. Mickiewicz in Vilna became a part of a typical Polish cultural discourse in the thirties on the topic of modern art and attitudes of the artists towards the romanticism tradition.